Inequality and Security in the Aftermath of Internal Population Displacement Shocks : Evidence from Nigeria - Ludolph, Lars; Šedová, Barbora; Talevi, Marta (World Bank, Washington, DC, 2022)
This paper studies the security implications of internal displacement shocks for host communities. It focuses on changes in wealth within host communities induced by the inﬂow of internally displaced persons (IDPs) as a potential mechanism that triggers local conflicts. The sudden insurgency of the jihadist terrorist organization Boko Haram, which led to the internal displacement of over 2.5 million persons in northeastern Nigeria, is used as a quasi-natural experiment. Applying both a two-way fixed effects analysis and an instrumental variable strategy based on historical ethnic ties between the areas of displacement and receiving areas, the results show that the presence of IDPs is associated with a decrease in aggregate wealth and an increase in inequality within host communities, between 2010 and 2019. These effects are accompanied by an increased risk of conflict onset in the short and long run. The inequality–conflict link is likely to be caused by grievances among low-wealth segments of the host community towards new arrivals rather than by changes in social cohesion within host communities, which increased in response to the inﬂow of IDPs. The analysis further indicates that an improvement in IDPs’ living conditions is accompanied by a decrease in violence and improved relations between hosts and IDPs. Taken together, findings from this study call for a two-pronged immediate relief and recovery approach that alleviates adverse economic effects on vulnerable segments of host communities and increases IDPs’ welfare in displacement settings.